Readiness for professional practice among health professions education graduates: a systematic review - Wynne, Katie; Mwangi, Felista; Onifade, Oyepeju; Abimbola, Omotola; Jones, Fiona; Burrows, Julie; Lynagh, Marita; Majeed, Tazeen; Sharma, Dileep; Bembridge, Elizabeth; Stubbs, Michelle; Sunner, Carla; et al. (Frontiers in Medicine, 2024)
Readiness to practice is the state of being prepared and capable of engaging in professional activities in a specific field. Graduates of healthcare professions require a diverse set of skills, knowledge and attitudes to meet the demands of complex healthcare settings. This systematic review provides a comprehensive analysis of readiness for professional practice among graduates of health professions education. It encompasses a wide range of articles published between 2013 and 2024, incorporating various health professions and utilizing a combination of quantitative, qualitative, and mixed methods designs. The review identified 93 studies from 32 diverse countries. The review revealed that factors influencing readiness to practice, include individual capabilities, the workplace context, and educational provision. It also explored strategies to enhance readiness to practice. The findings underscore the significance of addressing challenges such as lack of confidence, stress, communication, time management, job satisfaction, clinical experience, academic workload, teaching quality, mentorship and curriculum design. This comprehensive analysis serves as a valuable resource for healthcare educators, policymakers, and practitioners seeking to optimize the preparedness of graduates for the complexities of contemporary healthcare environments. Future studies should explore the interactions between readiness to practice stakeholders’ perception of the educational curriculum, and the quality of support in the professional practice environment.